NATURE OF NEW ORDER RIGHTS TO MINERALS: A RUBIKIAN EXERCISE SINCE PASSING THE MAYDAY RUBICON WITH A CUBIC ZIRCONIUM? - PJ Badenhorst (Obiter, 2022)
The Mineral and Petroleum Resources Development Act 28 of 2002 has created new categories of rights to “minerals” that may be granted to applicants by the Minister of Minerals and Energy. In this article the nature of these rights will be examined. The legislature has labelled prospecting rights and mining rights to minerals as limited real rights in the MPRD Act. The remaining rights to minerals are not labelled. Provision is made for registration or recording rights in the revived Mining Titles Registration Act 16 of 1967 (as amended). Registered rights are claimed to constitute a limited real right binding against third parties. Discrepancies and contradictions regarding the nature of rights to minerals are created by the two statutes. It is concluded that only upon clarification of the provisions of the two sister statutes, would the nature of rights to minerals be more evident. The proposed amendment of section 5(1) of the MPRD Act would be in line with property doctrine based upon the common law and is to be welcomed.